Intensive DNA sequence characterization of alleles at MCW0330 and LEI0094 Microsatellite Loci in chicken - Juan, Yin; Sheng-Cheng, Zeng; Yu-Zhu Luo; Han Jianlin (Science Alert, 2011)
To understand DNA sequence structural variation and its relationship with allelic distribution pattern obtained from genotyping data of microsatellite markers, Polymerase Chain Reaction (PCR) products of major alleles at two supposedly simple di-nucleotide chicken microsatellite loci of MCW0330 and LEI0094 were directly sequenced. The new sequences were compared with published data retrieved from the GenBank and Ensembl databases. The results showed that repeat unit at LEI0094 locus was a simple di-nucleotide of (AC)n for most alleles while the remaining alleles had their (AC) n irregularly interrupted by one or two (GA) nucleotides. On the other hand, MCW0330 locus carried a very complicated compound microsatellite consisted of three big structural blocks as its repeat units. These units consisted of CACAGACACA, CAGACACA and CTCAGACA. A few SNPs detected in upstream flanking sequences and specific combinations of basic structural units in repeat sequences of MCW0330 and LEI0094 loci contributed to define not only alleles different in both fragment sizes and sequence structures but also to alleles of the same fragment sizes but different in sequence structures that may lead to different peak patterns observed during genotyping exercise. Such ‘cryptic’ alleles of the same sizes but different in sequences can lead to an underestimated value in diversity and an ascertainment bias in interpreting microsatellite data. Therefore, an intensive characterization of DNA sequences in major microsatellite alleles derived from different genetic backgrounds is warranted to understand the evolutionary mechanism of different microsatellite DNA markers.